Circadian Clock-Specific Roles for the Light Response Protein WHITE COLLAR-2 - Collett, Michael A. (American Society for Microbiology, 2001)
To understand the role of white collar-2 in the Neurospora circadian clock, we examined alleles of wc-2 thought to encode partially functional proteins. We found that wc-2 allele ER24 contained a conservative mutation in the zinc finger. This mutation results in reduced levels of circadian rhythm-critical clock gene products, frq mRNA and FRQ protein, and in a lengthened period of the circadian clock. In addition, this mutation altered a second canonical property of the clock, temperature compensation: as temperature increased, period length decreased substantially. This temperature compensation defect correlated with a temperature-dependent increase in overall FRQ protein levels, with the relative increase being greater in wc-2 (ER24) than in wild type, while overall frq mRNA levels were largely unaltered by temperature. We suggest that this temperature-dependent increase in FRQ levels partially rescues the lowered levels of FRQ resulting from the wc-2 (ER24) defect, yielding a shorter period at higher temperatures. Thus, normal activity of the essential clock component WC-2, a positive regulator of frq, is critical for establishing period length and temperature compensation in this circadian system.